Nanopore sequencing and assembly of a human genome with ultra-long reads - Jain, M.; Koren, S.; Miga, K.H.; Quick, J.; Rand, A.C.; Sasani, T.A.; Tyson, J.R.; Beggs, A.D.; Dilthey, A.T.; Fiddes, I.T.; Malla, S.; Marriott, H.; et al. (Nature Publishing Group, 2018)
We report the sequencing and assembly of a reference genome for the human GM12878 Utah/Ceph cell line using the MinION (Oxford Nanopore Technologies) nanopore sequencer. 91.2 Gb of sequence data, representing ~30× theoretical coverage, were produced. Reference-based alignment enabled detection of large structural variants and epigenetic modifications. De novo assembly of nanopore reads alone yielded a contiguous assembly (NG50 ~3 Mb). Next, we developed a protocol to generate ultra-long reads (N50 > 100kb, up to 882 kb). Incorporating an additional 5×-coverage of these data more than doubled the assembly contiguity (NG50 ~6.4 Mb). The final assembled genome was 2,867 million bases in size, covering 85.8% of the reference. Assembly accuracy, after incorporating complementary short-read sequencing data, exceeded 99.8%. Ultra-long reads enabled assembly and phasing of the 4 Mb major histocompatibility complex (MHC) locus in its entirety, measurement of telomere repeat length and closure of gaps in the reference human genome assembly GRCh38.